A novel piezoelectric RF-MEMS resonator with enhanced quality factor. (31st January 2022) - Li, Jinchao; Chen, Zeji; Liu, Wenli; Yang, Jinling; Zhu, Yinfang; Yang, Fuhua
Abstract: This work presents a novel ultra-high frequency Lamb mode Aluminum nitride piezoelectric resonator with enhanced quality factors ( Q ). With slots introduced in the vicinity of the tether support end, the elastic waves leaking from the tether sidewalls can be reflected, which effectively reduces the anchor loss while retaining size compactness and mechanical robustness. Comprehensive analysis was carried out to provide helpful guidance for obtaining optimal slot designs. For various resonators with frequencies ranging from 630 MHz to 1.97 GHz, promising Q enhancements up to 2 times have all been achieved. The 1.97 GHz resonator implemented excellent f × Q product up to 6.72 × 10 12 and low motional resistance down to 340 Ω, which is one of the highest performances among the reported devices. The devices with enhanced Q values as well as compact size possess potential application in advanced radio frequency front end transceivers.